Atomic-scale insights of the effect of growth temperature on the migration behavior of Al atoms in InGaAs/AlGaAs multiple quantum wells. (February 2023) - Hao, Xiaodong; Li, Lei; Kong, Qingbo; Ma, Shufang; Wang, Jiahui; Xu, Yang; Liu, Xingyu; Han, Bin; Qiu, Bocang; Xu, Bingshe
Abstract: The growth temperature is a vital role in determining the overall crystal quality of the InGaAs/AlGaAs multiple quantum wells (MQWs) by regulating the migration of atoms at the interfaces, particularly the group (III) elements. In this study, two samples of InGaAs/AlGaAs MQWs were grown by the metal-organic chemical vapor deposition (MOCVD) method in the growth temperatures of 515°C and 650°C, respectively, and the effect of growth temperature on the interfacial structure of MQWs was investigated using high-resolution X-ray diffraction (HRXRD), atomic force microscopy (AFM) and photoluminescence (PL). Moreover, the state-of-the-art aberration-corrected scanning transmission electron microscopy (Cs-STEM) technique is also used to observe the atomic structure at the well-barrier interface, particularly the migration behavior of Al atoms, to deeply discuss the effect of the growth temperature on the interface structure of InGaAs/AlGaAs MQWs, and subsequently the optical performance.